Is your medical device “easy to use”? Supplemental oxygen patients’ experiences and tradeoffs around portable oxygen concentrators and tanks - Marc Egeth; Naomi Cherne; Nichole Breeland; Samantha Sye; Jennifer Soosaar; Frederic Seifer; Stanislav Glezer (Human Factors in Healthcare)
Engineering constraints on supplemental oxygen devices lead to tradeoffs for patients simply because larger and heavier devices last longer: larger tanks hold more oxygen, and the duration of use of a portable oxygen concentrator (POC) is governed by the size of its battery. Since a perfectly lightweight and long-lasting device cannot exist, the field seeks to optimize device options to suit the needs, desires, and lives of patients. The research described in this paper aims to understand through semi-structured interviews the experiences and interests of oxygen patients with respect to travel, mobility, and use of oxygen tanks and portable and stationary oxygen concentrators. We know that patients prefer devices that are “easy to use,” and we sought to clarify what this means and to prepare a more standardized measure of ease of use by developing an Absolute Ease of Use Scale for oxygen users. We also know that patients want a lightweight and long-lasting device, but we challenged patients to choose from specific lighter and heavier options associated with various battery lives. We probed where patients travel with their devices – and asked where else they would travel, if only their devices could be even lighter and last longer. Overall, a diverse picture emerges of widely varying preferences for time/weight tradeoffs and strategies for travel with these devices.